2016
DOI: 10.1002/gcc.22395
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Genetic Transitions of Copy Number Alterations and Allelic Imbalances in Oral Tongue Carcinoma Metastasis

Abstract: Primary tumor (PT) heterogeneity can significantly affect the genetic profile of clones at metastatic sites. To understand the mechanisms underlying metastasis, we compared the genetic profile of paired PT and metastatic lymph node (MLN) samples obtained from patients with oral tongue squamous cell carcinoma (OTSCC). Large-scale genetic profiling was performed on paired PT-MLN samples obtained from 10 OTSCC patients using high-density single-nucleotide polymorphism microarrays. We compared the genetic profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A methylation profile revealed that hypermethylation of microRNA (miRNA/miR)-10b with downregulation of its target gene nuclear receptor subfamily 4 group A member 3 was associated with tongue tumor patient survival ( 17 ). An additional study employed single-nucleotide polymorphism microarrays with human OTSCC samples to indicate that genetic changes, such as 20q11.2 gain encoding the E2F transcription factor 1 gene, may be acquired through clonal evolution and may be responsible for metastasis ( 18 ). miR-424 was reported to be a marker specific for tongue tumorigenesis, which also may function in the development of OTSCC ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…A methylation profile revealed that hypermethylation of microRNA (miRNA/miR)-10b with downregulation of its target gene nuclear receptor subfamily 4 group A member 3 was associated with tongue tumor patient survival ( 17 ). An additional study employed single-nucleotide polymorphism microarrays with human OTSCC samples to indicate that genetic changes, such as 20q11.2 gain encoding the E2F transcription factor 1 gene, may be acquired through clonal evolution and may be responsible for metastasis ( 18 ). miR-424 was reported to be a marker specific for tongue tumorigenesis, which also may function in the development of OTSCC ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although both CKS2 and DUT were significantly upregulated in TSCC, the mechanisms underlying their dysregulation have not been well understood. Gene‐level amplification was a common mechanism of gene upregulation in TSCC 29,30 . Our analysis based on data from 123 TSCC cases in TCGA indicated that gene‐level amplification might be an important mechanism of upregulated CKS2 and DUT .…”
Section: Discussionmentioning
confidence: 81%
“…Accumulating evidence has shown that the growth, invasion, and metastasis of malignant tumor are a multilink, multistep progression (Morita et al., 2016). In light of this, we detected the expression of SPC18 and EGFR pathway‐related proteins and found that overexpression of miR‐873‐5p could downregulate the expression of SPC18, p‐EGFR/EGFR, p‐Akt/Akt, and p‐ERK1/2/ERK1/2, while overexpression of SEC11A resulted in the upregulation of these proteins.…”
Section: Discussionmentioning
confidence: 99%